Assistência multiprofissional em Unidades de Terapia Intensivas Neonatais acreditadas em nível de excelência - Bruna Figueiredo Manzo (2012)
The survival of organizations in a globalized and competitive market is undoubtedly a major challenge in health care. Management systems focused on quality are now used aiming at the competitive potential and the institutional success for reducing costs and increasing profits. Thus, it can be noticed a mobilization on the implementation of quality programs in the hospitals in order to optimize the management of people and improve the efficiency of services. Importantly, the process of accreditation is a strategic senior management and this policy decision is passed on to professionals at all levels of hierarchy for the operation and performance of the idealized goal. Health professionals have prominent role in the implementation of processes to evaluate quality and its discursive and social practices reflect the daily work and directing actions to meet the needs of patients, mainly when it comes to seriously ill children in neonatal intensive care unit, since they present efficiency in the services. The professionals behavior can affect the way in which each service experiences the process, with influence on the decrease or increase in membership and progress of quality management. Although the hospital accreditation for many managers is presented as a legitimate ideology of quality and structures by rules and regulations, the subjects should also be appreciated especially with regard to the discourse of daily practices and not only under the requirements of the structures. Thus, this study aimed to analyse the configuration of the discursive practice of the accreditation process in the multidisciplinary team in neonatal intensive care units accredited at the level of excellence. It was chosen a qualitative approach using the theoretical post-structuralism reference. The research was conducted with health care professionals who develop their activities in two different neonatal intensive care units, but both believed in excellence, though interviews with a semi-structured script. The results which were taken from the discursive practices of the subjects showed that the two units presented more similarities than differences, although they have different histories and trajectories. They obtained the title of accreditation for excellence in different moments and present a scenario permeated by gaps and shortcomings, mainly regarding the differences between the requirements of the accreditation Manual and the actual experienced daily by multidisciplinary teams. It was noticed that, initially, the professionals trusted in the proposal and invested in preparation and in the accreditation process, focusing on changings, despite the pressure, but after successive evaluations there were loss of motivation and appreciation of the initiative by those who operate the system. It was also turned out, a fragmented and mechanized work process with a concentration on planning and decision making in industry leaders, and the difference in engagement between the professional categories. It is emphasized that the reality is very different from the calculated recommended for hospital accreditation ongoing maintenance of quality. The preparation process for the evaluation is focused on the moments preceding the visit of evaluators and under-valued in the intervals between assessments, which leads to discouragement and distrust of the professionals. So, it confirmed the argument of critics of the quality management that compare to the Taylor model, noting that the new process provides just another label, but no change in reality. Moreover, it is stressed that the purpose of analysis of the study was not to discourage the use of regulatory structure or to show an undesirable quality system. It was intended to actually submit a reflection on the discursive practices of the professionals on the hospital accreditation in the neonatal intensive care units, as important qualitative indicator of the attitude of the guys who put it into practice on the system from end clientele. It was concluded Assistência Multiprofissional em Unidades de Terapia Intensivas Neonatais Acreditadas em Nível de Excelência that the discursive practices are not consistent with the theory spread by quality management and that there is a large gap between recommended and actual quality, put into practice. In general terms there is a need for restructuring of work processes in the unit by means of strategies and management tools, with an appreciation of the subjectivity of workers to fill the gap between the requirements of the accreditation manual and the actual care offered by the multidisciplinary team.